Some Considerations Relevant to Prefunded Pensions in France - Levy, Joaquim (Washington, D.C. : International Monetary Fund, 1995)
Increasing use of life insurance instruments and company-sponsored funds in France suggests that French households may be inclined to a greater reliance on financial savings as a source of retirement income. This paper examines the challenges imposed by an aging population on the pay-as-you-go basic and supplementary pension systems, the growth of life insurance and company-sponsored funds in the absence of a comprehensive legislation on prefunded pensions, and issues related to prefunding pension schemes, such as the possibility of an welfare enhancing transition to prefunding; effects on capital markets in view of the experience in other OECD countries; and the importance of the transportability of pensions and measures fostering competition in financial markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet